TM1-1 Seizure prophylaxis in gliomas (SPRING): a phase III randomised controlled trial comparing prophylactic levetiracetam versus no prophylactic anti-epileptic drug in glioma surgery. Issue 3 (14th February 2019) - Jenkinson, MD; Watts, C; Marson, AG; Hill, R; Murray, K; Vale, L; Bulbeck, H; Grant, R
Abstract : Objectives: There is no consensus regarding the need for prophylactic anti-epileptic drug (AED) in seizure-naive newly-diagnosed glioma patients. Data regarding prophylactic AED use are scant and inconclusive from older, small studies that enrolled patients with brain metastases, benign tumours and gliomas. A definitive randomised controlled trial (RCT) is needed to determine whether the policy of prophylactic AED therapy reduces the risk of first seizures in this population. Design: Multi-centre RCT. Subjects: Inclusion criteria: i. seizure-naive, ii. supratentorial glioma suitable for surgery (biopsy/resection), iii. age ≥16 years; iv. Karnofsky performance status >60. Methods: Patients are randomised 1:1. Levetiracetam 500 mg bd for 2 weeks, increased to 750 mg bd thereafter for 1 year. Non-blinded. No placebo. Primary Outcome: one year risk of first seizure. Secondary outcomes: time to first seizure, time to first tonic-clonic seizure, mood, fatigue, quality of life, progression free survival, overall survival and incremental cost per QALY. Estimate of 1 year seizure rate in glioma after surgery is 20%. Based on a reduction in seizure rate to 10% a total of 806 patients will be recruited. Results: Grant awarded by NIHR. Feasibility questionnaire demonstrated prophylactic AED rarely used. Neurosurgeons willing to randomise. 15 UK centres have expressed interest in participating. Conclusions: SPRING will establish class I evidence for the use of seizure prophylaxis in glioma surgery. The trial will open to recruitment in January 2019.